Comprehensive security in Asia : views from Asia and the West on a changing security environment - Radtke, Kurt W. (Kurt Werner), 1945-; Feddema, Raymond (Brill, 2000)
This is an examination of "Comprehensive Security" as a policy that goes beyond the requirements of military defence against a particular "enemy" to stress the need to take into account other aspects vital to national stability: food, energy, environment, communication and social security.